Temperature-induced reactivation of Marek's disease virus-transformed T cells ex vivo - Tien, Yung-Tien; Akbar, Haji; Jarosinski, Keith William (Frontiers in Veterinary Science, 2023)
Marek’s disease virus (MDV) establishes latency in chicken T lymphocytes that can lead to T cell transformation and cancer. Transformed Marek’s disease chicken cell lines (MDCCs) can be expanded ex vivo and provide a valuable model to study latency, transformation, and reactivation. Here, we developed MDCCs from chickens infected with MDV that fluoresce during lytic replication and reactivation. Sodium butyrate treatment increased fluorescent protein expression as evidenced by fluorescent microscopy, flow cytometry, and western blotting; however, it caused significant apoptosis and necrosis. Treatment of MDCCs by decreasing the temperature resulted in robust MDV reactivation without significant induction of apoptosis and necrosis. Furthermore, MDV reactivation was significantly affected by the time in culture that can affect downstream reactivation analyses. In all, our data show that fluorescent protein expression during reactivation is a robust tool to examine viral replication in live cells ex vivo, and temperature treatment is an efficient technique to induce reactivation without punitive effects on cell viability seen with chemical treatment.